Activation of the endoplasmic reticulum stress response in skeletal muscle of G93A*SOD1 amyotrophic lateral sclerosis mice - Chen, Dapeng; Wang, Yan; Chin, Eva R. (Frontiers in Cellular Neuroscience, 2015)
Mutations in Cu/Zn superoxide dismutase (SOD1) are one of the genetic causes of Amyotrophic Lateral Sclerosis (ALS). Although the primary symptom of ALS is muscle weakness, the link between SOD1 mutations, cellular dysfunction and muscle atrophy and weakness is not well understood. The purpose of this study was to characterize cellular markers of ER stress in skeletal muscle across the lifespan of G93A*SOD1 (ALS-Tg) mice. Muscles were obtained from ALS-Tg and age-matched wild type (WT) mice at 70d (pre-symptomatic), 90d and 120-140d (symptomatic) and analyzed for ER stress markers. In white gastrocnemius (WG) muscle, ER stress sensors PERK and IRE1α were upregulated ~2-fold at 70d and remained (PERK) or increased further (IRE1α) at 120-140d. Phospho-eIF2, a downstream target of PERK and an inhibitor of protein translation, was increased by 70d and increased further to 12.9 –fold at 120-140d. IRE1α upregulation leads to increased splicing of X-box binding protein 1 (XBP-1) to the XBP-1s isoform. XBP-1s transcript was increased at 90d and 120-140d indicating activation of IRE1α signaling. The ER chaperone/heat shock protein Grp78/BiP was upregulated 2-fold at 70d and 90d and increased to 6.1-fold by 120-140d. The ER-stress-specific apoptotic signaling protein CHOP was upregulated 2-fold at 70d and 90d and increased to 13.3-fold at 120-140d indicating progressive activation of an apoptotic signal in muscle. There was a greater increase in Grp78/BiP and CHOP in WG vs. the more oxidative red gastrocnemius ALS-Tg at 120-140d indicating greater ER stress and apoptosis in fast glycolytic muscle. These data show that the ER stress response is activated in skeletal muscle of ALS-Tg mice by an early pre-symptomatic age and increases with disease progression. These data suggest a mechanism by which myocellular ER stress leads to reduced protein translation and contributes to muscle atrophy and weakness in ALS.